Analysis of the Components of a Hope-for-Life Training Package Based on Acceptance and Commitment Theory in Adolescents with High-Risk Behaviors - Esmaeliepour, Mahtab; Yousefi, Zahra; Farhadi, Hadi (Mental Health and Lifestyle Journal, 2024)
This study was conducted with the aim of analyzing the components of a hope-for-life training package based on Acceptance and Commitment Theory (ACT) among adolescents exhibiting high-risk behaviors. Accordingly, this research employed a qualitative design using the content analysis method of Hsieh and Shannon (2005). The research corpus included all texts related to hope for life and Acceptance and Commitment Theory. Based on the criterion of saturation, ten texts were selected according to predetermined inclusion and exclusion criteria. These texts were analyzed using the five-step method of Hsieh and Shannon (2005). The findings of the study indicated that hope for life in adolescents consists of several core concepts, including: (1) behavioral regulation (problem-solving, goal-directed behavior, self-efficacy, and interpersonal skills); (2) emotional regulation (acceptance of negative emotions and mindfulness); and (3) cognitive regulation (positive thinking, optimism, and cognitive flexibility). The content analysis of texts related to Acceptance and Commitment Theory revealed six core dimensions of the theory: (1) acceptance, (2) present-moment awareness, (3) cognitive defusion from dysfunctional thoughts, (4) values clarification, (5) setting and pursuing effective goals, and (6) self-as-context. These six dimensions were documented and recurrent across the literature. The components of the training package were derived from the integration of the two sets of concepts from the two content analyses and were presented as follows: cognitive defusion from ACT was aligned with enhancing cognitive regulation; three training components—living in the present moment, values identification, and committed action—were identified as related to behavioral regulation. Finally, acceptance of negative emotions and present-moment awareness were associated with the domain of emotional regulation. Based on these results, it can be concluded that the concepts of hope for life in adolescents are integrable within the framework of Acceptance and Commitment Theory.